The Influence of Perceived Value and Ease of Use on Brand Loyalty: The Mediating Effect of User Satisfaction - Fistarika Della Amanda; Astrid Puspaningrum; Ikhtiara Kaideni Isharina (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid evolution of digital banking in Indonesia has intensified competition between purely digital banks and conventional banks embracing digitalization. In this landscape, brand loyalty has emerged as a crucial factor for ensuring business sustainability. This study aims to investigate the impact of perceived value and ease of use on brand loyalty, with user satisfaction serving as a mediating variable, focusing on customers. A quantitative research design was applied using survey data from 213 respondents in Surabaya and Malang, collected through purposive sampling. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method via SmartPLS 4.0. The findings reveal that perceived value significantly and positively influences both user satisfaction and brand loyalty. Conversely, ease of use shows a significant negative relationship with brand loyalty and has no significant impact on user satisfaction. Moreover, user satisfaction positively affects brand loyalty and mediates the link between perceived value and brand loyalty, but not between ease of use and brand loyalty. The results suggest that customer loyalty in digital banking is primarily driven by perceived value and satisfaction rather than by ease of use alone.